Expert System for Identifying Weeds on Oil Palm Plantations Using a Web Based Forward Chaining and Dempster Shafer Method - Hastuti; Eny Maria; Annafi Franz (TEPIAN, 2022)
an expert system for identifying weeds on oil palm plantations using a web-based forward chaining and dempster shafer method. Palm oil is one of the plants that has its own charm in the community because the commodity of palm oil plays an important role in the Indonesian economy, therefore demand for palm oil continues to increase. Along with the increasing demand for palm oil in the world market, oil palm plantations have experienced many disturbances, one of which is weeds which are very detrimental to oil palm farmers, so oil palm farmers are trying to control it. Therefore, the purpose of this research is to build a system application that can be used by farmers to provide information related to weeds that attack oil palm and their control solutions.